2009
DOI: 10.1088/0004-637x/699/1/l13
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Sharp Edges and Planar Areas of Asteroids by Polyhedral Abrasion

Abstract: While the number of asteroids with known shapes has drastically increased over the past few years, little is known on the the time-evolution of shapes and the underlying physical processes. Here we propose an averaged abrasion model based on micro-collisons, accounting for asteroids not necessarily evolving toward regular spheroids, rather (depending on the fall-back rate of ejecta) following an alternative path, thus confirming photometry-derived features, e.g. existence of large, relatively flat areas separa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Here we show that the abrasion of a primordial asteroid by a huge number of tiny particles ultimately leads to such elongated shape. The model (called the Eikonal equation) predicting this outcome was already suggested in Domokos et al (2009) to play an important role in the evolution of asteroid shapes.…”
Section: Introductionmentioning
confidence: 92%
“…Here we show that the abrasion of a primordial asteroid by a huge number of tiny particles ultimately leads to such elongated shape. The model (called the Eikonal equation) predicting this outcome was already suggested in Domokos et al (2009) to play an important role in the evolution of asteroid shapes.…”
Section: Introductionmentioning
confidence: 92%
“…However, in our size range the geometric mean of their amplitudes appears to be roughly constant. Both Domokos et al (2009) and Henych & Pravec (2015) simulated the effect of subcatastrophic collisions on the elongation of small asteroids (D < 20km). They demonstrated that the cumulative effect of collisions should lead to an increase in the target object's elongation, occurring over shorter timescales at smaller sizes.…”
Section: Asteroid Elongation Dependence On Sizementioning
confidence: 99%
“…In their opinion, this is in agreement with the predictions of an impact-driven evolution of the asteroid shapes (KA03). Domokos et al (2009) studied the role of microcollisions on the overall shape of asteroids in their averaged continuum abrasion model. Their asteroid models evolve to prolonged shapes that possess large, flat areas separated by edges.…”
Section: Introductionmentioning
confidence: 99%